SISTEM INFORMASI REAL TIME PEMAKAIAN ENERGI LISTRIK - Asmawaty Azis (STMIK KHARISMA Makassar, 2015)
In this research software is designed that can provide information about the use of electrical energy in real time.In the electrical information system current sensor and voltage sensor will provide input to the microcontroller. This microcontroller has been included a program to control the hardware of the supporting system components. After the microcontroller processes the input from the current sensor and the voltage sensor, then the data will be displayed to the LCD. To store data used a laptop that functions as a server.The results of this study are to display the amount of energy used in each room of a boarding house in real time. The results obtained are the average discrepancy between the theoretical calculations with the results of the system is an average of 0.04% - 6.3%